2016
DOI: 10.1177/1541931213601138
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medical Education

Abstract: Virtual simulation is an emerging field in medical education. Research suggests that simulation reduces complication rates and improves learning gains for medical residents. One benefit of simulators is their allowance for more realistic and dynamic patient anatomies. While potentially useful throughout medical education, few studies have explored the impact of dynamic haptic simulators on medical training. In light of this research void, this study was developed to examine how a Dynamic-Haptic Robotic Trainer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…The study presented here represents a subset of a larger study that was conducted in summer and fall 2017 to compare the effectiveness of the DHRT system and current manikin simulators 18 . Only the purposes, procedures, methods, and participant information that are relevant to the current investigation are described here.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study presented here represents a subset of a larger study that was conducted in summer and fall 2017 to compare the effectiveness of the DHRT system and current manikin simulators 18 . Only the purposes, procedures, methods, and participant information that are relevant to the current investigation are described here.…”
Section: Methodsmentioning
confidence: 99%
“…This baseline scenario was used in a previous study which showed that the robotic trained novices in the 2016 residency cohort showed significant improvement in performance between the first and last needle insertion – which were both the baseline 27 . The manikin training condition was used in a larger study to compare the effectiveness of the DHRT system and current manikin simulators 18 and thus will not be considered for this study. In addition, the current investigation only considers performance on the first set of 10 needle insertions on the DHRT system to compare novices and expert surgeons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations